Penerapan Etika Islam Dalam Ilmu Di Bidang Teknologi Pengaruhnya Terhadap Hasil Belajar Bagi Mahasiswa FKIP UMSU - Sakinah, Nur; Balqish, Aisyah (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
Ethics is the main foundation in developing a technology, ethics is also very important in every application of a Muslim's behavior, without good ethics a Muslim is not a Muslim and a human is not a human being. The good personality that humans have indicates that they have good ethics as well. Therefore ethics is very important in the behavior of a Muslim because ethics affect human life in dealing with other social beings. Ethics is also one of the main foundations in developing a technology because ethics and technology are interrelated. Ethics is a positive basic attitude towards the possibility of various discoveries and ideas appearing. While technology is a step in the application of new discoveries in real results that are more modern and sophisticated so that they can encourage people to continue to develop even more advanced technology. This research aims to: 1). Knowing and understanding the characteristics of Islamic ethics in the application of knowledge in the field of technology for UMSU FKIP students; 2). So that UMSU FKIP students know ethics in the application of science in the field of technology; 3). Knowing the influence of Islamic ethics in the application of science in the field of technology for UMSU FKIP students in PGSD D, E IV Morning classes.